Bancassurance in India: An Alternative Channel of Insurance Distribution - Viswanadham, G. P. (Indian Journal of Marketing, 2005)
Bancassurance is the distribution of Insurance products through the bank's distribution channel. It is a phenomenon wherein insurance products are offered through the distribution channels of the banking services along with a complete range of banking and investment products and services. This paper examines the relevance of bancassurance in Indian context and makes a SWOT analysis of the same as an alternative channel of insurance distribution.